<span>Let x be the second number.
Let 2x+7 be the first number.
x+2x+7=25
3x+7=25
3x=25-7
3x=18
x=18/3
x=6
2x+7=19
The two numbers are 19 and 6.</span>
Answer:
(c) 43.
Step-by-step explanation:
Given:
Margin of error (E) = 2
Sample variance
= 44
Confidence level = 95%
The z- value at 95% confidence level is 1.96.
The sample using the provided information can be calculated as:
![n=(\frac{z(s)}{E})^{2} \\n=\frac{z^{2} s^{2} }{E^{2} } \\n=\frac{1.96^{2} (44) }{2^{2} }\\n= 42.52\\n=43](https://tex.z-dn.net/?f=n%3D%28%5Cfrac%7Bz%28s%29%7D%7BE%7D%29%5E%7B2%7D%20%5C%5Cn%3D%5Cfrac%7Bz%5E%7B2%7D%20s%5E%7B2%7D%20%7D%7BE%5E%7B2%7D%20%7D%20%5C%5Cn%3D%5Cfrac%7B1.96%5E%7B2%7D%20%2844%29%20%7D%7B2%5E%7B2%7D%20%7D%5C%5Cn%3D%2042.52%5C%5Cn%3D43)
Hence, the correct option is (c) 43.
Answer:
y =5x
Step-by-step explanation:
![y_{1}-y_{2} = m(x_{1} - x_{2} )](https://tex.z-dn.net/?f=y_%7B1%7D-y_%7B2%7D%20%20%3D%20m%28x_%7B1%7D%20-%20x_%7B2%7D%20%29)
(5 - 0) = m(1 - 0)
5 = m(1)
5 = m
![y_{1}-y_{2} = m(x_{1} - x_{2} )](https://tex.z-dn.net/?f=y_%7B1%7D-y_%7B2%7D%20%20%3D%20m%28x_%7B1%7D%20-%20x_%7B2%7D%20%29)
y - 5 = 5(x - 1)
y - 5 = 5x - 5
y = 5x -5 + 5
y = 5x